An International Scoping Review on Inclusive Education From Multiple Perspectives: Co-creating Inclusive Experiences in Shared Occupational Situations - Echsel, Angelika; Hocking, Clare; Jones, Margaret; Schulze, Christina (Informa UK Limited, 2025)
A human rights approach to inclusive education acknowledges that every learner has a fundamental right to access educational opportunities. For this scoping review, inclusion is defined from an occupational perspective as a concern with what people do together. The purpose of the study was to investigate the ways people can act to influence inclusion from the viewpoint of children, under the age of 18, parents, classroom and therapy staff and others. Children is defined as all children under the age of 18. Twenty-six studies representing 14 countries met the inclusion criteria. The findings focus on shared occupational situations, the extent to which these situations can be changed (their changeability) and the ways the social context shapes children’s experiences of more inclusive schooling. The findings suggest the need to shift to a more nuanced understanding of inclusive practices, while acknowledging the diversity of such practices within specific cultural contexts internationally.
Keywords: 39 Education; 3904 Specialist Studies In Education; Pediatric Research Initiative; 4 Quality Education; 1303 Specialist Studies in Education; 1608 Sociology; Education; 3902 Education policy, sociology and philosophy; Human rights; Dewey; inclusive education; student perspective; occupation